Avaliação pós-transcricional do gene FLO1 no processo de floculação de Saccharomyces cerevisiae - Leão, Olga Vitória Pereira (2016)
Saccharomyces cerevisiae was the second eukaryotic organism to have its genome sequenced and has been used for several decades as a model for cellular and molecular studies. This yeast is directly responsible for the transformation of sugar into ethanol and carbon dioxide, being one of the most used microorganisms in the fermentation industry. Flocculation is a phenomenon in which the yeast cells group and sediment rapidly in the medium in which they are suspended. It is a very complex process and depends on numerous factors such as the characteristics of the medium (pH and the presence of cations), conditions of fermentation (oxygenation, sugars, growth temperature, and the ethanol concentration) and the expression of genes of the FLO family. The process involves the interaction of specialized cell wall proteins called floculins, and carbohydrates (receptors) in the cell wall of neighboring cells. Previous studies have shown that both flocculent and non-flocculent strains present different expression of FLO gene family (FLO1, FLO8, FLO 10 and FLO11) in the logarithmic and stationary phases of growth, thereby demonstrating that even the nonflocculent strains induce expression of genes related to flocculation process. The objective of this study was to evaluate the translation of one of these genes, FLO1, level of production of Flo1 proteins and its subcellular localization. The results showed the expression of Flo1 floculina in the cell wall of the three strains of S. cerevisiae. These results go against literature data that attribute the flocculant phenotype to the presence of Flo proteins in the cell wall and the profile of non-flocculant yeast to the absence of floculin, demonstrating that other factors are related to the phenotype of flocculation. Thus, the results may contribute to a better understanding of flocculation and to the upgrading of fermentation processes.